Structural Study of a La(III) Complex of a 1,2,3-Triazole Ligand with Antioxidant Activity - Mauricio Alcolea Palafox; Nataliya P. Belskaya; Lozan T. Todorov; Irena P. Kostova (MDPI AG, 2023)
The 1,2,3-triazole derivative 2-(4-chlorophenyl)-5-(pyrrolidin-1-yl)-2H-1,2,3-triazole-4-carboxylic acid with potential anticancer activity was used as a ligand in complex formation with the lanthanum(III) ion. The molecular structure and vibrational spectra of the complex were optimized at three DFT levels, and the scaled IR and Raman spectra were compared to the experimental ones. Several scaling procedures were used. Through a detailed analysis, the structure predicted for the newly synthetized La(III) complex was confirmed by the good accordance of the calculated/experimental IR and Raman spectra. The best DFT method appeared to be M06-2X with the Lanl2mb basis set, followed closely by Lanl2dz. The effect of the lanthanide atom on the molecular structure and atomic charge distribution of the triazole ring was evaluated. The potential free radical scavenging activity of both the ligand and the complex was investigated in several radical-generating model systems. The potential mechanisms of antioxidant action (hydrogen atom transfer (HAT) and single-electron transfer (SET)) were elucidated.